1981
DOI: 10.1152/ajpgi.1981.240.1.g25
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic stimulation and blockade in colonic circulation of the rhesus monkey

Abstract: Adrenergic stimulation and blockade on inferior mesenteric arterial blood flow (Q) were measured in anesthetized rhesus monkeys. Control Q was 25 +/- 2 (mean +/- SE) ml/min; aortic and portal venous pressures were 121 +/- 5 and 6.5 +/- 1.0 mmHg. Calculated inferior mesenteric arterial resistance was 5.10 +/- 0.42 peripheral resistance units. Norepinephrine (N), 10(-3) to 1.0 microgram/kg intra-arterially, caused dose-dependent decreases in Q. Epinephrine (E) increased Q at 10(-3) microgram/kg in 60% of the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Haemorrhage of the order of 50% could reduce splanchnic blood flow by 40%, the anastomotic leak increasing when the blood pressure fell below 50 mmHg (Schrock et al 1973). Kerr & Swan (1981) have shown that alpha-adrenergic receptor stimulation causes vasoconstriction and beta stimulation causes vasodilatation in the colonic circulation, implying that beta-adrenergic blocking agents may be deleterious to the blood supply of the colon.…”
Section: Anaesthesiamentioning
confidence: 99%
“…Haemorrhage of the order of 50% could reduce splanchnic blood flow by 40%, the anastomotic leak increasing when the blood pressure fell below 50 mmHg (Schrock et al 1973). Kerr & Swan (1981) have shown that alpha-adrenergic receptor stimulation causes vasoconstriction and beta stimulation causes vasodilatation in the colonic circulation, implying that beta-adrenergic blocking agents may be deleterious to the blood supply of the colon.…”
Section: Anaesthesiamentioning
confidence: 99%